Searching for super - Jensen, Marion (HarperCollins Children's Books, an imprint of HarperCollins Publishers, 2015)
"The superheroes of Split Rock are hunkering down, which is really just a fancy way of saying they're hiding. Ever since those supervillainous Joneses took away their real powers, the Baileys and the Johnsons have been living in fear. But Rafter has had a taste of what saving the day feels like, and now he's desperate to do something important. So when he gets an opportunity to fight with a real superpower - as long as he promises not to tell his parents - he is going to take it, no questions asked. With the help of his brother Benny, his cousin Thimon, and his best friend, Juanita, Rafter Bailey is searching for super. Filled with heart and humor, Searching for Super is a family adventure of heroic proportions"--Publisher's website.